Tensions and inequalities: central and local policies towards urban and rural territories in Portugal and new approaches with the pandemic - Almeida, Maria Antónia (Eura 2021 Online Conference "Contradictions Shaping Urban Futures. Sustainable vs unsustainable urban development and growth vs degrowth”, 2021)
Urban concentration by the seashore, and particularly in Lisbon and Porto, has always been a feature of the Portuguese landscape. However, since the 1960s a huge rural exodus has resulted in a now irreversible depopulation of 80% of the Portuguese territory, where less than 20% of the population lives. Local government has played an important role in the development of attraction strategies for people, families and private companies, as well as many public policies by the central government have been put in place in order to revert this trend or at least to try to provide services and possibilities for a better quality of life for the remaining few who still resist urban attraction. At the same time, recently, as a result of insecurity in other areas of the world and with the prospect of quality of life and lower prices, there has been a huge boom in tourism and foreign investments in urban seashore cities, particularly Lisboa and Porto, resulting in the gentrification of city centres. How has local government dealt with these novelties? What are the differences between projects and political programs for urban and rural municipalities? Attraction strategies of municipalities and private entrepreneurs are analysed and compared. We discuss public policies and some contrasts and inequalities which have been addressed by municipalities and central government and local responses to the new pandemic situation.